Solve the simultaneous equations: y - 3x + 2 = 0 y^2 - x - 6x^2 = 0

y = 3x -2(3x-2)2 - x - 6x2 = 0 9x2- 12x + 4 - x - 6x2 = 03x2 - 13x + 4 = 0(3x - 1)(x-4) = 0 x = 1/3 or x = 4then y = -1 when x = 1/3 and y = 10 for x = 4

Answered by Katy D. Maths tutor

9005 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

evaluate the integral 2x/((9+x^2)^1/2) between -2 and 0


What does differentiating do?


Solve the equation 3^(5x-2)=4^(6-x), and show that the solution can be written in the form log10(a)/log10(b).


Given that log_{x} (7y+1) - log_{x} (2y) =1 x>4, 0<y<1 , express y in terms of x.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences